2008
DOI: 10.4314/gjas.v40i1.2147
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemistry and haematology of weaner rabbits fed sun-dried, ensiled, and fermented cassava peel-based diets

Abstract: Twenty-four New Zealand white × Chinchilla weaner bucks, aged between 7 and 8 weeks and averaging 0.9 kg in weight, were divided into four groups of six each and used in a 12-week feeding trial to evaluate the blood biochemistry and haematology of rabbits fed sun-dried, ensiled, and fermented cassava peel-based diets. The test diets designated A, B, C and D were completely randomised. Diet A, the control, was a 16.18 per cent CP (crude protein) weaner ration formulated from maize, maize offals, soya bean meal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
24
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 4 publications
14
24
4
Order By: Relevance
“…The values of ALT obtained in this study agreed with the normal range of 10.00 to 45.00 (iu/l) reported by Merck (2012). However, the values of ALT obtained in this study disagreed with the range 9.17 to 12.80 iu/l reported by Ahamefule et al (2006), they fed rabbits with sundried, ensiled and fermented cassava peel based diets. The normal value of ALT obtained in this study indicates that the activities of osteoblast were not affected because the blood level of ALT is usually a good indicator of the rate of bone formation.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The values of ALT obtained in this study agreed with the normal range of 10.00 to 45.00 (iu/l) reported by Merck (2012). However, the values of ALT obtained in this study disagreed with the range 9.17 to 12.80 iu/l reported by Ahamefule et al (2006), they fed rabbits with sundried, ensiled and fermented cassava peel based diets. The normal value of ALT obtained in this study indicates that the activities of osteoblast were not affected because the blood level of ALT is usually a good indicator of the rate of bone formation.…”
Section: Resultscontrasting
confidence: 99%
“…The values of AST obtained in this study were within the normal range of healthy rabbits 10 to 120 iu/l as reported by University of Pennsylvania School of Veterinary Medicine (2002). However, the values of AST obtained in this study were higher than the range of 7.73 to 16.0 iu/l reported by Ahamefule et al, (2006). They fed weaner rabbits sundried, ensiled and fermented cassava peel based diets.…”
Section: Resultscontrasting
confidence: 81%
“…However, GKSM significantly (P < 0.05) reduced lymphocytes and enhanced eosinophils of the rabbits. The values of the indices were, however, within the ranges reported as normal for rabbits (MacNamee and Sheeley, 1952;Mitruka and Rawnsley, 1977;Kathy, 2003;Ahamefule et al, 2006). The findings are in agreement with the earlier reports of Uko et al (2001) and Adedeji et al (2005) on the effects of Garcinia kola seeds on blood profile of rats.…”
Section: Haematological and Serum Biochemical Indicessupporting
confidence: 91%
“…The differential counts (%) of monocytes, lymphocytes, basophils, neutrophils and eosinophils were also not significantly different (P>0.05). The values are similar and fall within the normal range for health rabbits as reported by Ahamefule et al (2006). The normal differential counts (%) values portray the nutritional status of the rabbits, thus indicating adequate nourishment of the subjects (Chuch et al, 1984).…”
Section: Results and Discussion Haematological Indices And Differentisupporting
confidence: 68%